KINERJA SATUAN POLISI PAMONG PRAJA PROVINSI SULAWESI TENGAH DALAM PENGUATAN TUGAS SATUAN PERLINDUNGAN MASYARAKAT - Bulo, Anita (Katalogis, 2014)
The objective of the research was to analyze the performance of civil service unit of CentralSulawesi Province in duty enforcement on society protection unit  which reviewed through Lenvine model (1990: 43)  that emphasizing on aspects Accountability, Responsibility, and Responsiveness. This was a qualitative research with 6 informants selected purposively as the sample. The research results revealed that the performance of civil service unit of Central Sulawesi Province in duty enforcement on society protection unit was not optimal yet. It could be seen from the aspects. The first was accountability aspect showed that the consistency level of policy and the activity in civil service unit was not appropriate with society aspiration, the ability of increasing initiative and apparatus careness for the society dealing with target achievement was just at the beginning, the conflict level on society could not be minimized. The second was responsibility aspect showed that both civil service unit and society protection had not applied the administration principles orderly. It  was  due  to  the  principles  of  administration  that  have  not  applied  orderly,  namely:  (1) cooperation and coordination particularly concerning service quality of civil service unti to society protection had not run well, (2) service management concerning quality service of civil service unit to society protection was not maximally reached. The third was responsiveness aspect showed the maximal result of program and service give bybcivil service unit with the needs and aspiration of society protection members. The facators influencing the role of civil service unit against society protection could be seen from internal variables, such as: the first was human resources variable, they were lack either in quantity or in quality, the level of unqualified officers shoud be identified and adjusted to the field, and the lack of technical ability of the officers. The second was financial variable which lack   in funding duty and function and for supporting operational cost to reach mission and vision of organization. Those variables influenced the role of civil service unit against society protection.